UNIVERSITY NOTES. (The Accounting Review, 1926)
Abstract This article presents information related to account education in various universities. The accounting staff is developing its own text material for the first two years' work. New courses in accounting problems and auditing are being offered. George S. Clarksou, Certified Public Accountant (CPA), has given up his position as instructor in accounting in the evening division and Is now at Northeastern University in the same capacity. Henry J. Bornhofft, CPA., has been promoted to the rank of associate professor. James V. Toner has received the degree of M. A. from Holy Cross College and has been promoted to the rank of professor of accounting. Toner has collaborated with Professor Elwell in the revision of the Miner and Elwell Bookkeeping Series published by Ginn and Company. The revised text will be known as "Bookkeeping and Accounting" by Elwefl and Toner. N.S. Vincent, CPA., has resigned as Instructor in accounting is devoting his entire time to accounting practice. There have been no changes in the staff for this year. Accounting has been made a requirement for all students enrolled in the engineering college.